STEM-ESD Learning Based on Engineering Design Process and Reverse Engineering Toward Student Action on SDG-6 - Ayudya Fitriyani; Rini Solihat; Ari Widodo (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to analyze the effect of STEM-ESD learning—implemented through two engineering approaches, Engineering Design Process (EDP) and Reverse Engineering (RE)—on student action competency related to SDG-6 (clean water and sanitation) among secondary school students. Methodology: Mixed-methods convergent design. Participants: 108 students in three groups (two experimental: EDP and RE; one control; 36 per group). Instruments: action questionnaire, student worksheets, open-ended questionnaires, structured interviews. Analysis: descriptive statistics, Shapiro-Wilk normality test, Levene homogeneity test, one-way ANOVA, Kruskal-Wallis test. Main Findings: Neither EDP nor RE produced a statistically significant overall improvement in student action compared to the control group. However, at the indicator level: the RE group showed significant gains in competency achievement; the EDP group consistently outperformed others on current action and future action indicators. Both approaches demonstrate distinct, complementary mechanisms of influence. Novelty/Originality of this study: This study uniquely integrates STEM-ESD with two contrasting engineering approaches (EDP and RE) to address SDG-6, revealing their differential effects on student action competency. It advances knowledge by demonstrating that EDP and RE are not interchangeable but serve complementary functions—RE builds conceptual competence while EDP fosters action orientation and behavioral commitment.